KONTRIBUSI KREATIVITAS SISWA DAN SARANA PRASARANA TERHADAP HASIL BELAJAR MENERAPKAN DASAR-DASAR ELEKTRONIKA SISWA KELAS X TEKNIK ELEKTRONIKA INDUSTRIDI SMKN 4 PARIAMAN - Rahyuni Mutiya; Almasri Almasri; Nelda Azhar (Universitas Negeri Padang, 2017)
The background of this research is there are students acquire the learning outcomes below the minimum completeness criteria (KKM) is as much as 55.22%. KKM set schools on the subjects implementing the basics of electronics techniques is 75. The purpose of this study is to reveal the contribution of creativity of students and infrastructure against on learning outcomes.Type of this research is Descriptive Correlational. The study population numbered 67 students and a sample is 41 students. The technique of sampling was done randomly (Simple Random Sampling). Data on student learning outcomes obtained from the teachers implementing the basics of electronics grade X TEI in SMK Negeri 4 Pariaman, and data on creativity of students and infrastructure against collected through question naires distributed to students of class X TEI using the Likert Scale which has been tested for validity and reliability.The data is analyzed using statistical methods with software SPSS Version 16.0. The result showed that: 1) creativity of students and infrastructure jointly contributed 35.2% to the learning outcomes, 2) the creativity of students contributed 10.21% to the learning outcomes, 3) infrastructure against contributed 15,63% on learning outcomes. So the conclude is that creativity of students and infrastructure against together and partially contribute to student learning outcomes, its means that better creativity of students and infrastructure against, then the student learning outcomes obtained would increased. Keywords: Creativity of Students, Infrastructure Against, Learning Outcomes, and Simple RandomSampling.